Glutamatergic mechanisms in early salience processing - Lockhofen, Denise Elfriede Liesa; Hübner, Nils; Debnath, Ranjan; Rumpf, Karl Philipp; Sander, Michael; Wolff, Matthias; Luxi, Daniel; Roller, Lukas; Mulert, Christoph (Frontiers in Pharmacology, 2025)
IntroductionPatients with schizophrenia frequently experience inadequate attribution of motivational salience, possibly related to impaired attentional processing and dysfunctional reward learning. According to the “glutamate hypothesis of schizophrenia”, glutamatergic dysregulations can contribute to the emergence of psychotic symptoms and cognitive deficits in patients with schizophrenia. Blocking the N-methyl-D-aspartate receptor (NMDAR) with NMDAR antagonists such as ketamine can lead to temporary schizophrenia-like symptoms in healthy volunteers, including cognitive and attentional impairments.MethodThe present study investigated how the administration of a subclinical dose of ketamine compared to placebo affects the interaction of attention and reward. 27 healthy volunteers received either an intravenous infusion of ketamine or a placebo. Subsequently, an EEG was recorded while the subjects performed a visual attention task with salient, reward-related distractors.ResultsThe results demonstrate that ketamine primarily interfered with distractor processing, with little to no effect on target or reward processing. In addition, ketamine administration led to an increase in gamma band power compared to placebo and in salient distractor trials compared to target-only trials. Interestingly, these effects were related to the occurrence of negative symptoms.DiscussionTherefore, the present findings further emphasize the role of the glutamate system in the development of dysfunctional gamma band oscillations, early salience processing alterations and negative symptoms in patients with schizophrenia.